2018
DOI: 10.1590/1806-9061-2017-0523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Levels on Performance, Carcass Characteristics and Nutrient Digestibility of Sexed Broilers

Abstract: The objective of this study was to evaluate the effects of dietary nutrient levels on performance, carcass yield, commercial cuts, digestibility and economical viability of broilers from 1 to 42 days of age. During the experiment, 180 COBB 500™ chicks were housed in metal batteries and subjected to a completely randomized design in a 2x3 factorial arrangement, of two sexes and three diets (male, female and mixed), totaling 6 treatments and 6 repetitions of 5 birds each. Data were subjected to statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…Broilers fed feed P stored in dark room had higher dry matter, crude fat and fibre retention whereas higher crude protein and ash retention were recorded in broilers fed feed Q and S stored in dark room, respectively. The results in this study differed from those obtained by Lopez et al (2007), Sakomura and Rostagno (2016) and Muñoz et al (2018) who reported higher dry matter and lower crude protein digestibility in broilers chickens fed corn-soybean meal based diets. Differences in the digestibility of various feed brands employed in this study are in consonance with the reports of Uchegbu et al (2009).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Broilers fed feed P stored in dark room had higher dry matter, crude fat and fibre retention whereas higher crude protein and ash retention were recorded in broilers fed feed Q and S stored in dark room, respectively. The results in this study differed from those obtained by Lopez et al (2007), Sakomura and Rostagno (2016) and Muñoz et al (2018) who reported higher dry matter and lower crude protein digestibility in broilers chickens fed corn-soybean meal based diets. Differences in the digestibility of various feed brands employed in this study are in consonance with the reports of Uchegbu et al (2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Higher dressed yield percentage in broilers fed feed S stored in lit room further established the fact that availability of essential nutrients including amino acids (lysine, methionine and threonine), trace vitamins and minerals in adequate quantity are necessary for muscle tissue build-up and body maintenance (Alabi et al, 2017). Non-variation in carcass traits among broilers fed different feed brands agreed with the findings of Tavernari et al (2014) and Muñoz et al (2018) who reported that carcass yield was not influenced by the nutritional levels of the diets. In previous studies, Kamran et al (2008) reported no significant different in all carcass yield and relative organs weights in broilers fed low-protein diets with constant energy-to-protein ratio.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations